1954
DOI: 10.1002/path.1700680217
|View full text |Cite
|
Sign up to set email alerts
|

A study of 435 strains of Staphylococcus pyogenes with reference to factors which may contribute to pathogenicity

Abstract: IN an orthopaedic hospital there is a range of staphylococcal infections varying in site and severity, some remaining localised in the skin, others entering the blood stream and setting up abscesses in bone and elsewhere. This study was undertaken to find out whether strains which cause the more severe infections in man, particularly those MATERIALS AND NETHODS Strains were originally selected by the slide method of Cadness-Graves et al. (1943), but all were subeequently tested on plttsms-ww plates. Human plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1957
1957
1968
1968

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…In addition, strains of staphylococci, lethal to embryonated eggs, have been studied which fail to produce a-hemolysin either in vivo or in vitro (31). A similar situation is found in human infections where a-hemolysin, although produced by most staphylococci isolated from human infections, is not a prerequisite for human pathogenicity (42,43). Other exotoxins may be equally or more important than a-hemolysin in this experimental system, and attempts are in progress to delineate their role and the exact cause of death of the embryo.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, strains of staphylococci, lethal to embryonated eggs, have been studied which fail to produce a-hemolysin either in vivo or in vitro (31). A similar situation is found in human infections where a-hemolysin, although produced by most staphylococci isolated from human infections, is not a prerequisite for human pathogenicity (42,43). Other exotoxins may be equally or more important than a-hemolysin in this experimental system, and attempts are in progress to delineate their role and the exact cause of death of the embryo.…”
Section: Resultsmentioning
confidence: 97%
“…Kinase was demonstrated by the production of a clear zone on nutrient agar plates containing heated (20 min., 56') rabbit plasma (Lack & Wailling 1954). Soya bean trypsin inhibitor did not decrease the zone.…”
Section: -Toxin and Kinase In Staphylococci 323mentioning
confidence: 86%
“…They all produced hyaluronidase, although it has been shown that virulent strains may not produce hyaluronidase (Schwabacher, Cunliffe, Williams, and Harper, 1945). Lack (1956) has suggested that hyaluronidase may not act as a " spreading factor " but, by depolymerizing hyaluronic acid in connective tissue, it is removing a potential inhibitor. All the strains produced a haemolysin.…”
Section: Resultsmentioning
confidence: 99%